Two Years Under Jokowi – President’s Special Relationship with Luhut Panjaitan - Syailendra, Emirza Adi (2016)
Without networks within the military, and having no effective power over the political parties, President Joko Widodo (Jokowi) has been constrained in his political manoeuvres. He has, however, installed strong, well-networked, and experienced retired army generals, notably Luhut Binsar Panjaitan, as his aides. Is Jokowi dependent on him?